152k views
1 vote
Select the correct choice below and fill in any answer boxes in your choice.

Select the correct choice below and fill in any answer boxes in your choice.-example-1
User Ehds
by
4.8k points

1 Answer

1 vote

Given the equation:


(x+7)(x-2)=(x+1)^2

We will solve the equation as follows:


\begin{gathered} (x+7)(x-2)=(x+1)(x+1) \\ x(x-2)+7(x-2)=x(x+1)+1\cdot(x+1) \\ x^2-2x+7x-14=x^2+x+x+1 \\ x^2+5x-14=x^2+2x+1 \end{gathered}

Combine the like terms:


\begin{gathered} x^2-x^2+5x-2x=14+1 \\ 3x=15 \\ x=(15)/(3) \\ x=5 \end{gathered}

So, the answer will be option A:

The solution set is {5}

User Joseeight
by
4.6k points